Nurse Staffing and Care During the Immediate Postpartum Recovery Period. Issue 6 (November 2015) - Simpson, Kathleen Rice
Abstract : The first hours after birth are a time of joy and excitement, but also are associated with risk. What can you do to make sure the mother and baby are safe as they transition physiologically during the immediate postpartum recovery period? What standards and guidelines promote maternal and newborn safety during this time?